The Effect of Organizational Capacity For Change To Achieve High Performance Organization in Public Research Institutions: Evidence From BRIN Indonesia - Lastiwi, Danarsiwi Tri; Pradana, Aditya Wisnu; Wijaya, Chandra; Soeling, Pantius Drahen; Jatraningrum, Diah Anggraeni; Hastuti, Tri (STI Policy and Management Journal, 2024)
Strong organizational capacity is necessary to ensure a sustainable or enhanced performance during any form of change. In this regard, changing for achieving a high performance is a must for an institution. This study, through a case study at National Research and Innovation Agency (BRIN), aims to investigate the effect of organizational capacity of a public research institution for changes to achieve high R&D performance. Eight dimensions in Organizational Capacity for Change (OCC) and five dimensions in High Performance Organization (HPO) were examined. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results reveal that OCC significantly affected HPO at the 5% level, as the value of t-statistics > t-table (1.96). The influence of OCC was 0.875, meaning that an increase in the OCC resulted in a rise in HPO. Furthermore, the structural model of HPO produced an R-square value of 76.6%, reflecting the extent of the diversity of HPO that were able to be explained by the model used in this study, while the remaining (23.4%) were explained by factors outside the model. System Thinking (ST) was revealed as the most dominant dimension in OCC, indicating that BRIN’s capacity for change emphasizes the importance of aligning structures, processes, people, and policy to foster adaptability and resilience. Meanwhile, Management Quality (MQ) was revealed as the most dominant dimension in HPO, indicating that it facilitates smoother transitions in BRIN during the period of organizational change to achieve better R&D performance.